The Average Diameter of Coronary Artery in the Healthy Adult Population of Pakistan: A Cross-Sectional Study - Muhammad Hashim, Waqar Azim, Fazal Ur Rehman, Ahmed Ali, Dost Muhammad, Riffat Sultana (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the average diameters of the coronary arteries in the healthy adult population of Pakistan Study design: A cross-sectional study Place and duration: This study was conducted at Civil Hospital, BMCH Quetta Pakistan from March 2020 to March 2021. Methodology: A total of 120 participants were included in the study. All the patients included in the study were advised coronary angiography, nonetheless, their angiograms were normal. According to the inclusion criteria, the patients included in the study could be of any gender, above the age of 18 years, and have normal angiograms. The segments of the artery were divided as per the 29-segment model. The segments selected for the study were studied by the method of quantitative coronary angiography (QCA) method. Results: A total of 120 participants were considered in the study. The mean age of the included participants was 54.35±12.39 years. The mean of the Body Surface Area (BSA) was 1.78±0.163. The mean of the Body Mass Index (BMI) was 27.96±3.1 kg/m2. Proximal Left Circumflex (PLCx) and proximal left anterior descending (PLAD) were larger in diameter and the left main stem diameter was smaller. The Mid right coronary (MRCA) was greater in diameter, whereas the diameters of the proximal right coronary (PRCA), left main, distal left circumflex (DLCx), mid (MLAD), and distal (DLAD) were smaller. The MLAD, PLAD, PLCx, and DLAD had larger diameters and MRCA as well as the left main stem had smaller diameters. Conclusion: The diameters of the segments of the left stem of the coronary artery were smaller in the present study. Standardized data is needed for an accurate comparison.